The CRISPR-Cas system in Lactiplantibacillus plantarum strains: identification and characterization using a genome mining approach - Rostampour, Mohaddeseh; Panahi, Bahman; Masoumi Jahandizi, Reza (Frontiers in Microbiology, 2024)
Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (CAS) genes make up bacteria’s adaptive immune system against bacteriophages. In this study, 675 sequences of Lactiplantibacillus plantarum isolates deposited in GenBank were analyzed in terms of diversity, occurrence, and evolution of the CRISPR-Cas system. This study investigated the presence, structural variations, phylogenetic relationships, and diversity of CRISPR-Cas systems in 675 L. plantarum strains. The analysis revealed that 143 strains harbor confirmed CRISPR-Cas systems, with subtype II-A being predominant. Moreover, targeting phages and plasmid diversity between the predicted systems were dissected. The results indicated that approximately 22% of the isolates with verified and complete CRISPR systems exhibited the coexistence of both subtypes II-A and I-E within their genomes. The results further showed that in subtype II-A, the length of the repeat sequence was 36 nucleotides, on average. In addition, the number of spacers in subtypes II-A and I-E varied between 1–24 and 3–16 spacers, respectively. The results also indicated that subtype II-A has nine protospacer adjacent motifs, which are 5′-CC-3′, 5′-GAA-3′, 5′-TGG-3′, 5′-CTT-3′, 5′-GGG-3′, 5′-CAT-3′, 5′-CTC-3′, 5′-CCT-3′, and 5′-CGG-3′. In addition, the identified systems displayed a potential for targeting Lactobacillus phages. The investigation of the relationship between the targeting of Lactobacillus phages by the antiphage system in L. plantarum species showed that subtype II-A had the highest diversity in targeting Lactobacillus phages than subtype I-E. In conclusion, current findings offer a perspective on the prevalence and evolution of the CRISPR-Cas system in L. plantarum, contributing novel insights to the expanding field of CRISPR-Cas systems within lactobacillus strains. This knowledge establishes a foundation for future applied studies focused on enhancing phage resistance in industrial fermentation, reducing contamination risks, and improving product quality. The identified targeting diversity may also foster advancements in phage therapy through the development of CRISPR-based antimicrobials.